2021
DOI: 10.1007/s13760-021-01712-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of AQP4-NMOSD, MOGAD and seronegative NMOSD: a single-center Belgian cohort

Abstract: To emphasize physio-pathological, clinical and prognosis differences between conditions causing serious and sometimes very similar clinical manifestations: anti-aquaporin-4 (AQP4) and anti-myelin oligodendrocyte glycoprotein (MOG) antibodies related diseases, and seronegative NMOSD (neuromyelitis optica spectrum disorders).  Based on Wingerchuk et al. (Neurology 85:177–189, 2015) criteria for NMOSD and on those more recently proposed by Jarius et al. (J Neuroinflammation 15:134, 2018) for MOGAD (MOG associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…These findings suggest that the initial presentation had a higher predictive value for the clinical presentation of the second attack. Additionally, in the AQP4 antibody-positive children, younger patients were more likely to relapse with brain/brainstem onset than older patients (14), and this was clinically distinct from adult patients in that ON attack had more frequency at sequential attack (37,38). Also, our study demonstrated that TM onset was a potential predictor for TM recurrence at the second attack, and this phenomenon was observed in brain/brainstem onset as well but not found in the children with ON and mixed-lesion onset.…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that the initial presentation had a higher predictive value for the clinical presentation of the second attack. Additionally, in the AQP4 antibody-positive children, younger patients were more likely to relapse with brain/brainstem onset than older patients (14), and this was clinically distinct from adult patients in that ON attack had more frequency at sequential attack (37,38). Also, our study demonstrated that TM onset was a potential predictor for TM recurrence at the second attack, and this phenomenon was observed in brain/brainstem onset as well but not found in the children with ON and mixed-lesion onset.…”
Section: Discussionmentioning
confidence: 97%
“…A systematic review and meta-analysis has shown that eyes of AQP4-IgG + NMOSD patients with history of ON have worse visual acuity outcome when compared with those of MOGAD and MS patients [26], with other studies showing similar results [62][63][64][65][66]. In eyes with comparable pRNFL and GCIPL thinning, the degree of visual impairment in MOGAD patients is worse than that of MS patients but better than that of AQP4-IgG + NMOSD patients [64].…”
Section: Functional Damagementioning
confidence: 96%
“…Corticosteroids are used for acute attacks, while different other modalities, such as immunosuppressive medications, are used off-label as maintenance therapy. Although diagnostic criteria for the disease have been defined, CRION essentially remains a diagnosis of exclusion, as other demyelinating, autoimmune, and systemic causes should be ruled out first [ 1 , 2 , 3 , 4 , 5 ]. Despite the distinct clinical features characterizing CRION and NMOSD, such as a younger age of onset in CRION and female predominance in NMOSD, diagnosis remains challenging [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although diagnostic criteria for the disease have been defined, CRION essentially remains a diagnosis of exclusion, as other demyelinating, autoimmune, and systemic causes should be ruled out first [ 1 , 2 , 3 , 4 , 5 ]. Despite the distinct clinical features characterizing CRION and NMOSD, such as a younger age of onset in CRION and female predominance in NMOSD, diagnosis remains challenging [ 5 ]. CRION patients may be incorrectly diagnosed with relapsing-remitting multiple sclerosis (RRMS), neuromyelitis optica spectrum disorder (NMOSD), or multiple sclerosis (MS)-mimics.…”
Section: Introductionmentioning
confidence: 99%